The impact of plasma cholinergic enzyme activity and other risk factors for the development of delirium in patients receiving palliative care - Plaschke, Konstanze; Petersen, Katharina Angelika; Frankenhauser, Susanne; Weigand, Markus A.; Kopitz, Jürgen; Bardenheuer, Hubert J. (Journal of pain and symptom management, 2016)
Context - Delirium is an important complication in palliative care patients. One of the potential risk factors for cognitive disorders is deterioration in cholinergic neurotransmission. Anticholinergic medications are known to be important owing to the association of their metabolites with significant morbidity, which is often the result of cumulative effects of medications (anticholinergic burden). Additionally, cholinergic enzymes are possible candidates reflecting the cholinergic situation in patients. However, the role of cholinesterases (CHE) for delirium in palliative care patients is unknown. - Objectives - Following local Ethics Board approval and written informed consent, we recruited a cohort of patients who had been admitted to the Heidelberg University Palliative Care Unit related to CHE and other factors at risk for delirium. - Methods - Delirium was assessed using the Nursing Delirium Screening Scale once daily in all cancer patients (N = 100) during their stay on the palliative care unit. In a subgroup of 69 probes, blood samples were analyzed for acetyl- and butyrylcholinesterase activity spectrophotometrically. Furthermore, patients’ medications were recorded. Logistic regression analysis was used to evaluate potential predictors of delirium. - Results - Delirium was identified in 29% of patients. Karnofsky Performance Status Scale score was significantly lower (P = 0.021) and mortality higher (P = 0.018) in patients with delirium. Plasma CHE activity was not associated with delirium. However, a significant effect of anticholinergic medication on plasma CHE activity was detected; so far midazolam (P = 0.01) seems to play an important role in that process. - Conclusion - Special care might be necessary with anticholinergic medication to minimize risk for delirium in palliative cancer patients.